Bulinus snails in the Lake Victoria Basin in Kenya: Systematics and their role as hosts for schistosomes. - Caitlin R Babbitt; Martina R Laidemitt; Martin W Mutuku; Polycup O Oraro; Sara V Brant; Gerald M Mkoji; Eric S Loker (Public Library of Science (PLoS), 2023)
The planorbid gastropod genus Bulinus consists of 38 species that vary in their ability to vector Schistosoma haematobium (the causative agent of human urogenital schistosomiasis), other Schistosoma species, and non-schistosome trematodes. Relying on sequence-based identifications of bulinids (partial cox1 and 16S) and Schistosoma (cox1 and ITS), we examined Bulinus species in the Lake Victoria Basin in Kenya for naturally acquired infections with Schistosoma species. We collected 6,133 bulinids from 11 sites between 2014-2021, 226 (3.7%) of which harbored Schistosoma infections. We found 4 Bulinus taxa from Lake Victoria (B. truncatus, B. tropicus, B. ugandae, and B. cf. transversalis), and an additional 4 from other habitats (B. globosus, B. productus, B. forskalii, and B. scalaris). S. haematobium infections were found in B. globosus and B. productus (with infections in the former predominating) whereas S. bovis infections were identified in B. globosus, B. productus, B. forskalii, and B. ugandae. No nuclear/mitochondrial discordance potentially indicative of S. haematobium/S. bovis hybridization was detected. We highlight the presence of Bulinus ugandae as a distinct lake-dwelling taxon closely related to B. globosus yet, unlike all other members of the B. africanus species group, is likely not a vector for S. haematobium, though it does exhibit susceptibility to S. bovis. Other lake-dwelling bulinids also lacked S. haematobium infections, supporting the possibility that they all lack compatibility with local S. haematobium, thereby preventing widespread transmission of urogenital schistosomiasis in the lake's waters. We support B. productus as a distinct species from B. nasutus, B. scalaris as distinct from B. forskalii, and add further evidence for a B. globosus species complex with three lineages represented in Kenya alone. This study serves as an essential prelude for investigating why these patterns in compatibility exist and whether the underlying biological mechanisms may be exploited for the purpose of limiting schistosome transmission.